Strategi Metakognitif dalam Pembelajaran Kooperatif untuk Meningkatkan Kualitas Proses Pembelajaran Genetika di SMA - Endang Susantini (Universitas Negeri Malang, 2016)
The purposes of this study was to examine the effectiveness of Metacognitive Strategies in Cooperative Learning (MS-CL), compared to Metacognitive Strategies (MS), in genetics learning. A quasi-experiment design was applied in this study, involving 92 out of 230 third-year students of SMAN 6 Surabaya. Data were collected by means of achievement test and were then analyzed by analyses of covariance. The results indicated that the thinking skills of the students employing MS-CL were low, but their scores on genetics exam were not significantly different from those employing MS. However, the MS-CL was found to develop students colaborative skills. The students with high ability showed higher thinking skill and higher score on genetics exam than students with low ability.